(3cJGH aj GdUQas ((3EdjGS Hf JZQi HQOi s)
(3ChdgG (B:s
(3jHOC HHGH GdJUQja s
(3BNQgG (B:s
(3heKdg CjVkG GdeNOY hgh HjJ UZjQ ai UOQ GdHjJ GdcHjQ hQhi CjVkG GdJKdjK ai eje eUMa hbO LYd fXe gPG GdHGH ecedkG CHhGH PG GdcJGH aGdMeO ddg Ydi Jcejdg s
(3HgG fXGe GdJYbjHIs
(3hgh TQM defXheIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
Keywords: (3GdUQas